Euglycemic Diabetic Ketoacidosis Induced by Sodium-glucose Cotransporter-2 Inhibitor in the Setting of Chronic Kidney Disease with Dehydration Induced by Nausea and Vomiting: A Case Report - Mahmoud, Emad Hamdi; Ismail, Olaa Awad (Archives of Case Reports, 2025)
Background: Euglycemic diabetic ketoacidosis (EDKA) is a recognized but uncommon adverse effect of sodium–glucose cotransporter-2 (SGLT2) inhibitors. It presents with metabolic acidosis and significant ketosis, yet with normal or near-normal blood glucose levels, making its diagnosis frequently delayed. SGLT2 inhibitors are increasingly used for their cardiovascular and renal benefits in patients with type 2 diabetes mellitus; however, clinicians should remain alert to this potential complication, especially when additional risk factors such as dehydration, fasting, or renal impairment coexist. Case presentation: We report the case of a 54-year-old male with long-standing type 2 diabetes mellitus, hypertension, and chronic kidney disease who developed euglycemic diabetic ketoacidosis following two days of nausea, vomiting, and poor oral intake. The patient had been on empagliflozin and pioglitazone therapy. On admission, he appeared dehydrated and mildly tachycardic. Laboratory findings revealed metabolic acidosis (pH 7.10, bicarbonate 15 mmol/L, with an elevated anion gap), positive serum ketones, and a normal blood glucose level of 9 mmol/L. After exclusion of other causes, the diagnosis of EDKA secondary to SGLT2 inhibitor use was established. Empagliflozin was discontinued, and the patient was treated with dextrose-containing intravenous fluids, continuous insulin infusion, and electrolyte replacement. His metabolic derangements resolved within 48 hours, and he was discharged in stable condition with appropriate counseling and outpatient follow-up. Conclusion: This case highlights the importance of considering EDKA in diabetic patients presenting with unexplained metabolic acidosis, even when glucose levels are not elevated. Recognition of SGLT2 inhibitor–induced EDKA is vital, particularly in the presence of precipitating factors such as dehydration and chronic kidney disease. Early identification and prompt management are crucial for preventing morbidity and mortality.